Stakeholder Theory: evolution and the proposal of a research agenda - Menezes, David Curtinaz (2022)
Objective of the study: to present an overview of the evolution of the Stakeholder Theory through the analysis of the main models of analysis and theoretical propositions in order to address the main questions that guide the debate on this theory.Methodology: literature review in which articles published in international and national journals related to the theme between 1980 and 2021 are analyzed.Originality/relevance: this research contributes to the debate on the Stakeholder Theory by systematizing the knowledge on this theoretical field and identifying gaps that configure a research agenda that will contribute to the advancement of that theory.Main results: the main issues related to that theory are identified, as well as a research agenda that involves: i) identification, prioritization and engagement of stakeholders; ii) accounting for the generation of value for all stakeholders; iii) the influence of these actors in the practices adopted by the organizations and in the decision making of the government; iv) the simultaneous influences of stakeholders and how the interactions between these actors influence the stakeholder management; and v) how to achieve better performance, equity and greater value creation for all stakeholders in proportion to their contribution to the organization.Theoretical/methodological contributions: this study, through the analysis of the development of the Stakeholder Theory, allows identifying perspectives for new studies and assisting researchers in understanding the main issues addressed in the field.